Poverty, Income Distribution, and Government Policy that Pro-Poor in Indonesia year 2009-2016 - Hayu Fadlun Widyasthika; Azwardi Azwardi; Tatang Abdul Madjid (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2017)
This study aims to determine the effect of growth and distribution on poverty change as well as to analyse whether expenditure growth has given the benefits to the poor and non-poor in urban and rural area. The data used are raw data from total household consumption obtained from National Socio-Economic Survey for the period of 2009 to 2016. Poverty decomposition is used to see the effect of income growth and distribution on the poverty change. Furthermore, Poverty Equivalent Growth Rate (PEGR) supported by Growth Incidence Curve (GIC) is used to determine whether the benefit of economic growth is enjoyed more by the poor compared to pro-poor growth or not. The results show that income growth influences the decrease in poverty both in rural and urban area in Indonesia, during 2009-2016, 2009-2014 and 2014-2016. Conversely, the distribution of income increases the poverty in both areas during the periods. Inequality of income seems to give a strong influence so that the economic growth has not been a pro-poor both in rural and urban area of Indonesia during 2009-2016, 2009-2014 and 2009-2016.